KUALITAS PELAYANAN UPTD PENERANGAN JALAN UMUM DALAM MENERAPKAN APLIKASI SIPUJAAN DI KABUPATEN SUMEDANG - Supriatna, Agus (JRPA - Journal of Regional Public Administration, 2024)
This study aims to determine the Quality of Service of UPTD Public Street Lighting in Implementing the SIPUJAAN Application in Sumedang Regency. The research method used in this research is qualitative research method. The technique of determining research informants is purposive sampling, with research informants, namely the Head of the Sumedang Regency Public Street Lighting UPTD, SIPPUJAAN Application Program Administrator, Street Lighting Maintenance Technician. Data collection techniques used, namely literature study and field studies consisting of observation, interviews, and documentation. While the data processing procedures in this study, namely data reduction, data display, data conclusion drawing / verification and triangulation Service Mechanism, the service process through the SIPUJAAN application has provided convenience for the community in reporting PJU damage. This mechanism replaces manual methods with a more effective digital system. Service Suitability, the services provided are in accordance with the needs of the community. Incoming complaints are handled based on the level of damage and availability of resources. Technical Capability and Competence, the service manager has competence in accordance with their duties, from administrators to technicians, so that damage, especially of a technical nature, can be handled professionally. Ability Feasibility, the technical capabilities possessed, especially in the electrical field, are sufficient to handle various levels of damage, both minor and severe. However, although the service quality of the SIPUJAAN application is quite good, continuous improvement is still needed to optimize the service. This improvement will have an impact on public satisfaction as the main indicator of public organization performance. With maximum service, it is expected that the quality and public trust in public services in Sumedang Regency will increase.